EFEKTIVITAS BIBLIOTERAPI KELOMPOK UNTUK MENURUNKAN KECEMASAN SOSIAL PADA REMAJA CERDAS ISTIMEWA - , ERNI AGUSTINA SETYOWATI; , Dra. Supra Wimbarti, M.Sc., Ph.D., Psi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Gifted adolescents have high cognitive ability, but sometimes they have difficulty in social or emotional aspects. One of their characteristics is being oversensitive when interacting with others. It may result in higher possibility to feel anxious in facing social situation than others. The purpose of this study was to examine the effectiveness of group bibliotherapy treatment to reduce social anxiety in gifted adolescents. Participants in this study were five adolescents, 11.9-13.3 years old, IQ >130 WISC scale who have social anxiety problem. They have taken part in province and national mathematics competition in Indonesian Science and Mathematics Olympiad (OSN: Olimpiade Sains Nasional) 2008 and 2009.One group pretest posttest design was used in this study. The experiment was conducted in seven sessions through Asyik Belajar Matematika 1-6 books. Have been rated by three raters, these books are to use properly for adolescent who have emotional or behavioral problem especially social anxiety. These books contain values related to subject problems. The data analyzed with Wilcoxon Signed Rank Test. The result showed that group bibliotherapy was effective to reduce social anxiety in gifted adolescent. Treatment gain were maintained at a-1 month follow-up. (p= 0.042